2001
DOI: 10.1111/j.1745-6584.2001.tb02342.x
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of a Natural Gradient Tracer Experiment for the Natural Attenuation Study: Flow and Physical Transport

Abstract: Results are presented for numerical simulations of ground water flow and physical transport associated with a natural gradient tracer experiment conducted within a heterogeneous alluvial aquifer of the Natural Attenuation Study (NATS) site near Columbus, Mississippi. A principal goal of NATS is to evaluate biogeochemical models that predict the rate and extent of natural biodegradation under field conditions. This paper describes the initial phase in the model evaluation process, i.e., calibration of flow and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 28 publications
2
55
1
Order By: Relevance
“…In response to the positively skewed tritium plumes which cannot be described by the classical ADE with a coarse-scale flow field [2], researchers have attempted to simulate the tracer plumes using many different methods in the last decade (see the review by Molz et al [107] and Zhang et al [148]). The commonly accepted conclusion is that the classical ADE with a fine-scale (such as decimeter-scale) flow field [51,93,125,152,153,155], or the dual-domain approach with a similarly fine resolution of flow field [53,69,75,107], may describe the anomalous plumes at the MADE site. However, the practicality of the first method is questionable due to limitations of current characterization techniques in differentiating between small-scale heterogeneities.…”
Section: Experiments 4: the Tritium Transport At The Made-1 Testmentioning
confidence: 99%
“…In response to the positively skewed tritium plumes which cannot be described by the classical ADE with a coarse-scale flow field [2], researchers have attempted to simulate the tracer plumes using many different methods in the last decade (see the review by Molz et al [107] and Zhang et al [148]). The commonly accepted conclusion is that the classical ADE with a fine-scale (such as decimeter-scale) flow field [51,93,125,152,153,155], or the dual-domain approach with a similarly fine resolution of flow field [53,69,75,107], may describe the anomalous plumes at the MADE site. However, the practicality of the first method is questionable due to limitations of current characterization techniques in differentiating between small-scale heterogeneities.…”
Section: Experiments 4: the Tritium Transport At The Made-1 Testmentioning
confidence: 99%
“…[36] The plausible hydrogeological explanation for the ''nonideal'' transport behavior observed at the MADE site supports three types of modeling methods, which include the following: (1) the second-order ADE with a fine-scale velocity field capturing both the multiscale flow paths and relatively immobile, trapping zones [Zheng and Jiao, 1998;Eggleston and Rojstaczer, 1998;Zheng and Gorelick, 2003;Zinn and Harvey, 2003;Liu et al, 2004]; (2) the dualdomain approach with a relatively coarse (upscaled) flow field [Harvey and Gorelick, 2000;Feehley et al, 2000;Julian et al, 2001]; and (3) novel nonlocal techniques, such as the CTRW method [Berkowitz and Scher, 1998] and the fADE method , which directly capture the anomalous transport process, using a very coarse, or even a constant, mean transport velocity. An exceptional case of the first method was discussed recently by Barlebo et al [2004], who showed that the second-order ADE with a simplified zonal conductivity (K) field can also characterize the positively skewed plume at the MADE site.…”
Section: Anomalous Transport and Previous Modeling Methodsmentioning
confidence: 99%
“…Review of the literature indicates that modeling of different kinds of contaminant has been studied by several researchers. Among them most prominent includes Wilber (1980), Copoulos and Sehayek (1986), Hutson and Wagenet (1989), Shifang (1991), Hooshmand (1992), Zheng and Bennett (1997), Feehley et al (2000), Holder et al (2000), Barth et al (2001), Boutt et al (2001), Elci et al (2001, Mehl and Hill (2001), Julian et al (2001), Shamrukh et al (2001), Faidi et al (2002), Zheng and Wang (2002), Andrews and Neville (2003), Bakker (2003), Brown and Glynn (2003), Conan et al (2003), Harrar et al (2003), Langevin (2003), Prommer et al (2003), Zheng and Gorelick (2003), Liu et al (2004), and Wang and Bright (2004). Risk assessments of the subsurface environment often involve the use of quantitative contaminant fate and transport models.…”
Section: Utility Of Numerical Solute Transport Models In Environmentamentioning
confidence: 98%